Effect of low temperature on growth and ultra-structure of Staphylococcus spp. - Laura A Onyango; R Hugh Dunstan; Johan Gottfries; Christof von Eiff; Timothy K Roberts (PLoS ONE, 2012)
The effect of temperature fluctuation is an important factor in bacterial growth especially for pathogens such as the staphylococci that have to remain viable during potentially harsh and prolonged transfer conditions between hosts. The aim of this study was to investigate the response of S. aureus, S. epidermidis, and S. lugdunensis when exposed to low temperature (4°C) for prolonged periods, and how this factor affected their subsequent growth, colony morphology, cellular ultra-structure, and amino acid composition in the non-cytoplasmic hydrolysate fraction. Clinical isolates were grown under optimal conditions and then subjected to 4°C conditions for a period of 8 wks. Cold-stressed and reference control samples were assessed under transmission electron microscopy (TEM) to identify potential ultra-structural changes. To determine changes in amino acid composition, cells were fractured to remove the lipid and cytoplasmic components and the remaining structural components were hydrolysed. Amino acid profiles for the hydrolysis fraction were then analysed for changes by using principal component analysis (PCA). Exposure of the three staphylococci to prolonged low temperature stress resulted in the formation of increasing proportions of small colony variant (SCV) phenotypes. TEM revealed that SCV cells had significantly thicker and more diffuse cell-walls than their corresponding WT samples for both S. aureus and S. epidermidis, but the changes were not significant for S. lugdunensis. Substantial species-specific alterations in the amino acid composition of the structural hydrolysate fraction were also observed in the cold-treated cells. The data indicated that the staphylococci responded over prolonged periods of cold-stress treatment by transforming into SCV populations. The observed ultra-structural and amino acid changes were proposed to represent response mechanisms for staphylococcal survival amidst hostile conditions, thus maintaining the viability of the species until favourable conditions arise again.